Pendidikan Anak Usia Dini (PAUD) Holistik Integratif - Fitri Wahyuni (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2019)
Education is universally understood as developing the full potential of humanity and the cultivation of socio-cultural values ​​that are believed by a group of people to be able to sustain life and life properly. To create a quality generation, the people really expect adequate education for their sons and daughters especially when they are still at the early age level. Early age is the most important and fundamental initial period throughout the growth and development of human life. At this time it was marked by various important fundamental periods in the life of the child, the next child until the final period of its development. one of the periods that becomes the character of an early age is the golden ages. Acceleration and expansion of PAUD services is one of the strategic policies passed by the national education ministry in line with the policy of adding and increasing the competence and capacity of PAUD education to become demands that cannot be ignored. A comprehensive integrative effort is needed to develop PAUD institutions so that being able to truly develop the potential of early childhood to achieve it requires high dedication from educators / family schools, communities, and the government